ANALYSIS OF GROUNDWATER VULNERABILITY TOWARD POLLUTANT FROM SEPTIC TANK BY UTILIZING FUZZY-DRASTIC METHOD (A CASE STUDY IN SLEMAN DISTINCT REGENCY, YOGYAKARTA) - JOKO PURNOMO (NIM : 22106321), BUDI
The settlements in Sleman Distinct Regency, DIY, commonly use septic tanks for disposing their domestic waste, hence potentially causing pollution toward the groundwater. The analysis of the vulnerability of the groundwater must pay a considerable attention to the natural condition (intrinsic vulnerability) and the condition of the source of pollutant (specific vulnerability). As for the spatial data, which are gradational in nature, the processing of the data need to use appropriate methods, one of which is fuzzy-logic method. The analysis of the vulnerability of the groundwater, perceived from the natural condition side (intrinsic vulnerability), was done by using DRASTIC method, by calculating the depth of the groundwater surface (D), the rainfall (R), types of aquifer media (A), texture of the soil (S), topography slopes (T), vadoze zone (I), and aquifer conductivity (C). The analysis of the pollutant source (specific vulnerability) septic tanks, was estimated based on the factor of the amount of septic tanks density which referred to the density of settlements and the factor of the volume/concentration of waste-disposals to septic tanks which referred to the population’s density. The combination of all components was done by utilizing fuzzy gamma operator. The analysis showed that most of the areas (63.7 % or 367.97 km2) in Sleman Distinct Regency had a considerably high natural vulnerability, as for the source of the pollutant (septic tanks) showed that 64 % of the settlements areas had low level of vulnerability. The territory which indicated the high level of vulnerability of the groundwater toward the pollutant from septic tanks existed in the center of the population’s activity (urban area), whose width was more or less 44,4 km2 or 27,8 % of the whole settlement areas.